ANALISIS PENJADWALAN PRODUKSI MENGGUNAKAN METODE CAMPBELL DUDEK SMITH DAN DANNENBRING DALAM MEMINIMUMKAN TOTAL WAKTU PRODUKSI BERAS - ANTARI, NI KADEK DESI PUJA; HARINI, LUH PUTU IDA; TASTRAWATI, NI KETUT TARI (E-Jurnal Matematika; Vol 10 No 4 (2021), 2021)
The increasing needs for basic materials has resulted in an increased production process of basic materials in a company. CV. Puspa is a manufacturing company engaged in the production of rice, on the production process, CV. Puspa often has a buildup of work so that it requires an alternative production scheduling optimally. This research was conducted to minimize the total time of completion using the Campbell Dudek Smith and Dannenbring method in determining efficient production scheduling. Based on the scheduling sequence obtained, the calculation results of the total completion time using the Campbell Dudek Smith method are less than or equal to the results of calculation using the Dannenbring method. So the Campbell Dudek Smith method is more efficient than the Dannenbring method to be applied to CV. Puspa.